Enrolment status disparity: evidence from secondary education in Myanmar. Issue 2 (2nd December 2019) - Yoshida, Natsuho
Abstract : Purpose: The purpose of this paper is to explore individual enrolment trajectories to fully understand the actual disparity in secondary education enrolment statuses among the different socio-economic status (SES) groups in a newly emerged nation, Myanmar. Design/methodology/approach: The differences in enrolment statuses among various SES groups (high, middle and low) were examined based on enrolment trajectory diagrams and individual enrolment patterns using longitudinal data. The analyses utilised a sample of 932 students from government schools in the urban Yangon Region. Findings: The results revealed that the ideal enrolment trajectory cases (i.e. entering secondary education at Myanmar's official age and completing all grades without repetition) increased for the highest-SES level, whilst the cases with diverse and complex enrolment trajectories increased for the lower-SES levels. Additionally, over-aged students in the lowest-SES level (boys in particular) were more likely to demonstrate worse enrolment patterns. Originality/value: By analysing disparities with enrolment trajectories rather than with the cross-sectional parity index, the findings offer clearer and more detailed evidence for the current enrolment status inequalities by SES level in Myanmar. This more complete evidence could allow for an effective accomplishment of worldwide equitable and universal secondary education.